Pengaruh media Pembelajaran 3D Street Story Map untuk Kemampuan Berpikir Spasial Siswa SMA - Sari, Rima Meilita; Urfan, Faiz; Ridhwan, Ridhwan; Herliza, Muna; Dani, Fadila Rahma; Br Sembiring, Tesalonika (Universitas Pendidikan Ganesha, 2023)
One of the geography skills is students have spatial thinking ability. The aim of this research is to develop 3D Street Story Map Learning Media to accelerate students' spatial thinking ability. Learning media developed based on Google My Map integrated with virtual tours so that learning media can be used in geography learning courses. The development uses a 4D model that is adjusted to development needs. The define phase examines the study of development needs including a literature study and needs assessment of high school students and teachers. The design stage contains four steps, including constructing criteria and references, selecting media, selecting formats, and initial design. The second stage is to develop and validate learning media from material and media experts and test the practicality of learning media. The research results are the creation of 3D Steet Story Map learning media which was developed based on a needs assessment study, tested validity based on the material and media experts, and has practical and effective value for student geography learning. The practical implications of using 3D Street Story Map learning media are in this article.